Denotational semantics for programming languages, balanced quasi-metrics and fixed points - Rodríguez-López, J.; Romaguera, S.; Valero, O. (International journal of computer mathematics, 2008)
A new mathematical model is introduced for the study of the domain of words. We do it by means of the introduction of a suitable balanced quasi-metric on the set of all words over an alphabet. It will be shown that this construction has better quasi-metric and topological properties than several classical constructions. We also prove a fixed point theorem which allows us to develop an application for the study of probabilistic divide and conquer algorithms.